Dimas’ Expression of His Identity as an Indonesian in Leila S. Chudori’s “Pulang” - Irene Priscilla Wibowo (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
In this study, I observe the way the character in Leila S. Chudori’s, Pulang, preserves his identity in a foreign country. In analyzing the novel, I use the theory of social symbols by George H. Mead. In the analysis, I find that Dimas uses symbols as Indonesians to preserve his identity. By doing so, he gets the acknowledgement by the Indonesian community as a part of its member even though he lives in different nation. This shows Dimas perceives his identity because he is aware that he is part of Indonesian community. As a result, Dimas can preserve his identity as an Indonesian even though he lives far away from Indonesia.